Uniaxial Compression Mechanical Properties of Rock Samples in Soft and Hard Composite Strata - Bo Wu; Wei Huang (Advances in Materials Science and Engineering)
In the upper soft and lower hard composite strata, it is very difficult to sample the rock and test the mechanical properties of the samples. The study of the mechanical properties of similar material samples by artificial manufacture may enable an alternative method to solve this problem. Therefore, the feasibility of artificial sample preparation and the test of mechanical properties of rock samples in the composite strata become the key to solve the study of mechanical properties of the upper soft strata and the lower hard composite strata. For this purpose, the artificial composite samples composed of two kinds of materials with different strengths were prepared by using cement and kaolin as similar materials. Through the uniaxial compression test of artificial composite rock samples, the effects of the strength ratio of similar materials and the thickness ratio of higher strength materials on the mechanical properties of composite specimens were analyzed. The results of uniaxial compression test show that artificial similar materials could be used to simulate the composite rock samples which are difficult to sample. Without considering the structural interface effect, the greater the strength ratio of similar materials, the greater the impact on the overall strength of composite specimens. The change of volume proportion of high-strength materials has a significant impact on the overall strength of composite specimens. Moreover, the numerical simulation and the experimental stress-strain curves both show a similar trend, indicating that the deformation of the composite strata mainly occurs in the soft part. The research results can provide reference for the test and analysis of mechanical properties in similar complex strata with difficult sampling.